La haute mer : un espace aux frontières de la recherche géographique - Camille Parrain (EchoGéo)
The high sea has been little studied within geography. Its characteristics show that it is a complex space and do reflect its alterity. The ocean is a difficult and original fieldwork that invites to be analyzed with interdisciplinary methods (geography, oceanography, climatology, biology, history, economy). The geographical approach has so far mainly been an applied geography and has focused on regional, sectorial and coastal aspects. Few are aiming at theoretical approaches or on the high seas. We will overview the position of the ocean within geography and will try to explore new research perspectives by taking into account sailing and the concept of territory in the high sea that we will define as « maritory ». To define it, we offer to discuss on the terms of mobility, discontinuity, network and seascape. Seascape - example of an interdisciplinary tool- could appear as a method for marine management.